Genome Editing with Crispr-Cas9 Systems: Basic Research and Clinical Applications - Anna Meiliana; Nurrani Mustika Dewi; Andi Wijaya (The Prodia Education and Research Institute (PERI), 2017)
BACKGROUND: Recently established genome editing technologies will open new avenues for biological research and development. Human genome editing is a powerful tool which offers great scientific and therapeutic potential.CONTENT: Genome editing using the clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPRassociated protein 9 (Cas9) technology is revolutionizing the gene function studies and possibly will give rise to an entirely new degree of therapeutics for a large range of diseases. Prompt advances in the CRISPR/Cas9 technology, as well as delivery modalities for gene therapy applications, are dismissing the barriers to the clinical translation of this technology. Many studies conducted showed promising results, but as current available technologies for evaluating off-target gene modification, several elements must be addressed to validate the safety of the CRISPR/Cas9 platform for clinical application, as the ethical implication as well.SUMMARY: The CRISPR/Cas9 system is a powerful genome editing technology with the potential to create a variety of novel therapeutics for a range of diseases, many of which are currently untreatable.KEYWORDS: genome editing, CRISPR-Cas, guideRNA, DSB, ZFNs, TALEN